Analisis Struktur Retorika Bagian Latar Belakang Skripsi Mahasiswa Program Studi Sistem Informatika Fakultas Teknik Universitas Muhammadiyah Bengkulu - Gunawan, Hafiz (UNIB Press, 2019)
The purpose of this study was to provide an understanding of the stages and steps of the background section of the thesis of the Information Systems Study Program Faculty of Engineering, University of Muhammadiyah Bengkulu. This research uses a descriptive method. Data is all written statements of students when writing a thesis. The data source in this study is the thesis of 20 students of the Information Systems Study Program at the Faculty of Engineering, University of Muhammadiyah Bengkulu. Data collection techniques using documentation techniques. The steps in the analysis of the research data are 1) coding, 2) reading all parts of the background, 3) identifying the background, 4) classifying stages and steps, 6) choosing a dominant pattern. Test the validity of the data using the expert validity test. The results of the research and discussion of the Rhetoric Structure of the Background Section of the Thesis of the Student Information Systems Study Program Faculty of Engineering, University of Muhammadiyah Bengkulu are; Stages in the background section of the thesis of the Information Systems Study Program of the Faculty of Engineering, University of Muhammadiyah Bengkulu that all theses used the stages in the PJP model, and the steps in the stages of the thesis background of the students of the Information System Study Program of the Faculty of Engineering, University of Muhammadiyah Bengkulu did not all use the steps steps in the PJP model stage. The findings can be used as input material in deepening insight and adding to the knowledge literature about the rhetorical structure of the background section of the thesis.